DEVELOPMENT OF INDONESIAN LEARNING MEDIA BY USING MICROSOFT POWERPOINT FOR STUDENTS OF CLASS VII SMP NEGERI 2 - Karina Oktaviana; Sutikno Sutikno; Rahmat Kartolo (Research Collaboration Community (RCC), 2022)
Learning media has an influence in efforts to increase student learning achievement. The selection of traditional learning media has begun to shift to modern and up-to-date learning media that are more practical, attractive, interesting, creative and innovative. This research was conducted to produce the development of writing materials and learning media for Indonesian language learning using Microsoft PowerPoint for class VII semester 2 students of SMP Negeri 2 Pegajahan. This type of development research data is in the form of qualitative data and quantitative data. The research uses the research and development (R&D) model of Borg and Gall. The purpose of this study is the compilation of a learning media product as an effort to develop writing materials. In connection with this goal, the researcher uses seven steps in developing learning media, namely analyzing the needs of teachers and students, product development with Microsoft PowerPoint, validation of media experts and material experts and language teachers Indonesia, the first phase of revision, field trials, and finally the final revision. The quality of learning media products can be known through the average obtained from the validation results from Indonesian language teachers of 95%. The average percentage of the assessment results is 87.18% with a very good category. In addition, the quality of development products can also be known through the results of excellent student feedback. The product of this research is learning materials and media designed for class VII SMP in the second semester. This product contains eight Competency Standards which are translated into seventeen Basic Competencies and contained in twelve lessons. The twelve lessons are structured and integrated with one main menu. Each media unit is arranged systematically including apperception, competency standards and basic competencies, indicators, materials, sample questions and competency tests in which there are various media that are arranged simultaneously including text, audio recordings, videos and animations. The results of this study are very relevant to the 2013 curriculum because it is in accordance with the standards of the interactive, inspiring, fun, creative, challenging and motivating learning process for students. Further research is needed to determine the effectiveness and influence of the use of this media on student achievement.